Additions to the Connaraceae of the state of Guerrero, Mexico - Jiménez-Ramírez, Jaime; Cruz-Durán, Ramiro (Instituto de Ecología, A.C., 2014)
The addition of Connarus stenophyllus Standl. et L.O. Williams ex Ant. Molina and C. lentiginosus Brandegee to the flora of Guerrero state, Mexico, is presented. Descriptions of both species are given as well as a key to distinguish them; herbarium specimens studied are also included.